FRI0612-HPR EFFECT OF THERMOFORMABLE ORTHOSES ON FOOT FUNCTION IN RHEUMATOID ARTHRITIS PATIENTS: PRELIMINARY RESULTS FROM AN OPEN CLINICAL TRIAL. (2nd June 2020) - Aachari, I.; Rkain, H.; Safaa, F.; Benzakour, L.; Latifa, T.; Alami, N.; Guieu, R.; Jammes, Y.; Hajjaj-Hassouni, N.; Allali, F.
Abstract : Background: Orthoses and footwear can play an important role in managing foot pathology in patients whose systemic disease is controlled. Foot orthoses are frequently prescribed in clinical practice as an intervention for people with rheumatoid arthritis (RA). Objectives: The aim of our study is to evaluate the impact of thermoformable orthoses on the functional index of the foot (FFI) in patients with rheumatoid arthritis. Methods: We conducted an open clinical trial, having consecutively included 14 patients (85.7% female, average age 54.8 ± 10 years) suffering from rheumatoid arthritis (median progression time of 9 years [5 - 12]). The average DAS28 was 2.7 ± 1.2 and the functional impact objectified by the Health Assessment Questionnaire (HAQ) was on average 0.9 ± 0.7. The median deadline from the start of RA and the onset of the foot problem was 3 years [0 – 7, 75]. The foot problem was bilateral in 100% of the cases and inaugural in 85.7% of the cases. We evaluated the functional impact of foot injury for all our patients at baseline and 8 weeks after the use of thermoformable orthoses, based on the FFI (Foot function Index) measuring the impact of foot pathology on function in terms of pain, disability and activity limitation. The comparison of the FFI domains before and after the use of orthoses was carried out using parametric or nonparametric paired tests using The SPSS statistical software. Results: With the use of foot orthoses, FFI values decreased in all subscales (p=0, 024) (pain, disability and activity limitation). This reduction was significant for disability (0, 011) but not for pain and activity limitation. There were no significant correlations between the global FFI and the progression of RA, the duration of foot damage and the functional impact measured by the HAQ. Table 1. The comparison of the FFI domains before and after the use of orthoses. p significatif if< 0, 05; Test used: Non-parametric test for two linked samples. Conclusion: Foot orthoses were effective as an adjuvant in the management of rheumatoid foot. They significantly reduced disability as measured by the FFI. The absence of factors associated with pain and limitation of activity could possibly be related to the small sample size. Disclosure of Interests: None declared